A comparative, sociotechnical design perspective on Responsible Innovation: multidisciplinary research and education on digitized energy and Automated Vehicles. Issue 3 (2nd September 2021) - Hess, David J.; Lee, Dasom; Biebl, Bianca; Fränzle, Martin; Lehnhoff, Sebastian; Neema, Himanshu; Niehaus, Jürgen; Pretschner, Alexander; Sztipanovits, Janos
ABSTRACT: This study develops a comparative, sociotechnical design perspective for interdisciplinary teams of social scientists and computer scientists. Sociotechnical design refers to identifying both technical and governance challenges and to understanding the ways in which the two types of problems affect and define each other. Approaching design as an open-ended, iterative process, the study develops a triple comparative perspective to problem finding and solutions: across two types of technological systems (the smart grid and connected and automated vehicles), three areas of societal implication and values (safety, equity, and privacy), and two continents (North America and Europe with a focus on the U.S. and Germany). The study then describes the implementation in an international collaboration of research and teaching. The collaborative experience and comparative research provide insights into the salience of the values across technological systems, portability of solutions across technological systems, and potential for policy harmonization across countries.